Kondisi Lingkungan Perairan Pada Lahan Budidaya Rumput Laut Kappaphycus alvarezii Di Desa Jayakarsa Kabupaten Minahasa Utara - Mudeng, Joppy D; Kolopita, Magdalena E.F; Rahman, Abdul (e-Journal BUDIDAYA PERAIRAN, 2015)
A research had been conducted to evaluate seaweed and waters condition at seaweedÂ  culture area at Jayakarsa Village.Â  Research locations were divided into three station: 1) at former culture area near mangrove area and the beach, 2)Â  at active culture area, 3) at former culture area with sandy bottom and â€lamunâ€ field.Â  Water quality measured included temperature, salinity, pH, DO, turbidity, flow rate, water depth, bottom type. Protectivenss, risk, and accesibility were also observed. Data was analyzed descriptively and then compared to standard value established in Kangkan (2006).Â  Water condition at station 1 and 2 was categorized Grade 2 (moderately suitable) while at station 3 was marginally suitable which was categorized Grade 3. Major problems faced by the farmers was ice-ice disease, silt and epiphytes that could reduce the production. Â  Keywords: Kappaphycus alvarezii, water quality, Jayakarsa Village, moderately suitable, marginally suitable